A review on the fabrication of electrospun polymer electrolyte membrane for direct methanol fuel cell - Junoh, Hazlina (Hindawi Publishing Corporation, 2015)
Proton exchange membrane (PEM) is an electrolyte which behaves as important indicator for fuel cell's performance. Research and development (R&D) on fabrication of desirable PEM have burgeoned year by year, especially for direct methanol fuel cell (DMFC). However, most of the R&Ds only focus on the parent polymer electrolyte rather than polymer inorganic composites. This might be due to the difficulties faced in producing good dispersion of inorganic filler within the polymer matrix, which would consequently reduce the DMFC's performance. Electrospinning is a promising technique to cater for this arising problem owing to its more widespread dispersion of inorganic filler within the polymer matrix, which can reduce the size of the filler up to nanoscale. There has been a huge development on fabricating electrolyte nanocomposite membrane, regardless of the effect of electrospun nanocomposite membrane on the fuel cell's performance. In this present paper, issues regarding the R&D on electrospun sulfonated poly (ether ether ketone) (SPEEK)/inorganic nanocomposite fiber are addressed.